Composite current collector, lithium ion battery and preparation method of base membrane
By distributing conductive agent in the base film of the composite fluid collector gradient, the polarization problem of excessive internal resistance and safety problem of excessive internal resistance of the composite fluid collector is solved, and the high-rate performance and safety performance are improved.
Patent Information
- Application Number
- CN202411527067.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-03
AI Technical Summary
The internal resistance of the composite liquid collector leads to polarization, which affects the rate performance of lithium-ion batteries; the internal resistance is too low, which reduces the safety performance and makes it difficult to fuse and protect the battery.
The composite fluid design with gradient distribution of conductive agent content is adopted. By increasing the content of conductive agent in the base film, the current density distribution is matched, thereby reducing internal resistance and improving safety.
It effectively reduces the internal resistance of the composite liquid collector, avoids polarization, improves the rate performance and safety performance of the battery, and ensures the stability and safety of the battery during high current charging and discharging.
Smart Images

Figure CN119252927A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite current collectors, and in particular relates to a preparation method of a composite current collector, a lithium ion battery and a base film. Background Art
[0002] The current collector is used to connect the tabs and collect the current generated by the battery active material to form a larger current output. The traditional current collector is made of pure metal (such as copper foil or aluminum foil), and its thickness is often around 12μm. Although it has good conductivity, it is difficult to fuse and protect the battery in the event of thermal runaway due to its large thickness. In addition, the current collector made of pure metal is heavy, which will reduce the energy density of the battery.
[0003] In this context, composite current collectors have appeared on the market. Composite current collectors are a kind of "sandwich" structure. The inner layer (base film) is a polymer high molecular layer (such as PET, PP or PI). The upper and lower surfaces of the inner layer are provided with metal conductive layers, among which the metal conductive layer of the positive current collector is aluminum foil, and the metal conductive layer of the negative current collector is copper foil. Specifically, the current mass-produced positive composite current collectors often use PP (polypropylene) as the base film, the thickness of the base film is 4-4.5μm, and the metal conductive layer copper layer on both sides of the base film is often provided on the upper and lower surfaces of the base film by magnetron sputtering, electroplating or evaporation, and the thickness of the copper layer is about 1μm. The negative composite current collector often uses PET (polyethylene terephthalate) as the base film, the thickness of the base film is about 6μm, and the metal conductive layer aluminum layer on both sides of the base film is often provided on both sides of the base film by evaporation, and the thickness of the aluminum layer is about 1μm.
[0004] Compared with traditional current collectors, the inner layer of the composite current collector uses a polymer material with a lower density. On the one hand, it can effectively reduce the weight of the composite current collector (for example, 50%-80% lower than traditional pure metal foil), thereby improving the mass energy density (for example, 5%-10% higher than traditional pure metal foil); on the other hand, since the metal conductive layer is only about 1μm, in the event of thermal runaway, the conductive layer will melt rapidly to form a "circuit-breaking effect", and the inner base film is an insulating layer, which can effectively prevent the positive and negative electrodes from short-circuiting, thereby significantly improving the safety performance.
[0005] However, as the metal layer of the current collector becomes thinner, its resistance will also increase. For example, when the thickness of the metal conductive layer of the composite current collector is about 2μm, its internal resistance is much greater than that of the traditional thicker metal foil current collector (such as copper foil or aluminum foil). Due to the large internal resistance, when the battery is charged and discharged with a large current, a large polarization phenomenon will occur (that is, the battery voltage deviates from its equilibrium state), causing the internal temperature of the battery to rise, seriously affecting the rate performance of the battery. Based on this, it is necessary to study the composite current collector to solve the above technical problems. Summary of the invention
[0006] The present invention provides the following technical solutions to solve the above technical problems.
[0007] The present invention provides a composite current collector, comprising:
[0008] a first conductive layer;
[0009] a second conductive layer;
[0010] Base film: located between the first conductive layer and the second conductive layer, the base film contains a conductive agent;
[0011] The composite current collector has a first end and a second end arranged opposite to each other along the length direction, the first end is connected to the pole ear, and the current density and the content of the conductive agent gradually increase from the second end to the first end; the content of the conductive agent = the mass of the conductive agent in the base film / the total mass of the base film in the area where the conductive agent is located.
[0012] The above technical solution can avoid the polarization problem caused by excessive internal resistance and the low safety problem caused by too low internal resistance.
[0013] Optionally, the length of the base film is L, the content of the conductive agent at the first end is k, wherein 0.2%≤k≤2%, the distance from the first end to any position of the base film is x, and the content of the conductive agent at x is k x , k x =(Lx) / L*k.
[0014] Optionally, the conductive agent is one or more of carbon nanotubes, acetylene black and conductive carbon black.
[0015] Optionally, the base film has a thickness of 3-10 μm, and the first conductive layer and the second conductive layer have a thickness of 0.5-3 μm.
[0016] The present invention also provides a lithium ion battery, comprising the composite current collector in any one of the above embodiments.
[0017] By adopting the above technical solution, a lithium-ion battery with high safety performance and good rate performance can be obtained.
[0018] The present invention also provides a method for preparing a base film, which is used to prepare the base film in the composite current collector in any of the above embodiments. The method adopts a slit extrusion coating die, and the slit extrusion coating die comprises a cavity and a plurality of feed ports, and the plurality of feed ports correspond to different positions of the cavity respectively. The method comprises:
[0019] Pretreatment: Conductive agents of different masses are mixed with molten polymer materials to obtain slurries with different contents of conductive agents; the polymer materials are selected from one or more of PET, PP or PI;
[0020] Feeding: Slurries with different contents of conductive agent obtained after pretreatment are fed into the cavity through different feed ports, and then the slurries are mixed to obtain slurries with gradient distribution of conductive agent content;
[0021] Coating: The slurry with a gradient distribution of conductive agent content is extruded and cooled to obtain a base film.
[0022] By adopting the above technical solution, the base film in the composite current collector in any of the above embodiments can be quickly prepared.
[0023] Optionally, the pretreatment step is: putting different masses of conductive agents and molten polymer materials into a double planetary mixer for stirring to obtain slurries with different conductive agent contents, wherein the stirring conditions are: rotation 2000-4000rpm, revolution 15-40rpm, and stirring time 30-40min.
[0024] Optionally, in the feeding step: the slurry is mixed for 5-20 seconds.
[0025] Optionally, the feeding step includes: feeding the slurries with different contents of conductive agent obtained after pretreatment into the cavity at a rate of 0.2-5 min / L.
[0026] Optionally, the volume of the cavity is 0.2L-2L. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A schematic diagram of the development of a composite current collector in the prior art is shown;
[0028] Figure 2 Schematic diagram showing the development of a composite current collector in one embodiment of the present invention Figure 1 ;
[0029] Figure 3 A schematic diagram showing the connection between the first end of the composite current collector and the tab in one embodiment of the present invention is shown;
[0030] Figure 4 Schematic diagram showing the development of a composite current collector in one embodiment of the present invention Figure 2 ;
[0031] Figure 5 A schematic diagram of the overall structure of a slot extrusion coating die in one embodiment of the present invention is shown.
[0032] (Explanation of symbols)
[0033] 1-composite current collector, 1.1-first end, 1.2-second end, 2-first conductive layer, 3-second conductive layer, 4-base film, 5-conductive agent, 6-ear, 7-slit extrusion coating die, 8-feed port, 9-die head, 10-coating roller, 11-lip, M-length direction. DETAILED DESCRIPTION
[0034] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0035] The terms “first”, “second”, etc. are only used for distinguishing descriptions and should not be understood as indicating or implying relative importance.
[0036] It should be noted that in this specification, similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings.
[0037] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0038] like Figure 1 As shown, in the prior art, the composite current collector 1 includes a first conductive layer 2, a second conductive layer 3 and a base film 4, wherein the base film 4 is located between the first conductive layer 2 and the second conductive layer 3. However, the composite current collector 1 has a problem of large internal resistance. To this end, the present invention provides the following technical solution to reduce the internal resistance of the composite current collector 1.
[0039] like Figure 2-Figure 3 As shown, the present invention provides a composite current collector 1, which includes:
[0040] A first conductive layer 2;
[0041] A second conductive layer 3;
[0042] Base film 4: located between the first conductive layer 2 and the second conductive layer 3, the base film 4 contains a conductive agent 5;
[0043] The composite current collector 1 has a length M (eg Figure 2 The first end 1.1 and the second end 1.2 are arranged opposite to each other in the M direction, the first end 1.1 is connected to the pole ear 6, and the direction from the second end 1.2 to the first end 1.1 (for example Figure 3 The current density of M1 in the film gradually increases and the content of the conductive agent 5 gradually increases, wherein the content of the conductive agent 5 = the mass of the conductive agent 5 in the base film 4 / the total mass of the base film 4 in the area where the conductive agent 5 is located.
[0044] The conductive agent 5 can improve the electronic conductivity of the battery electrode. The present invention reduces the internal resistance of the composite current collector 1 by adding the conductive agent 5 to the base film 4. However, if too much conductive agent 5 is added, the composite current collector 1 will be close to the traditional pure metal current collector, which will make it difficult to fuse and protect the battery in the event of thermal runaway, and will also reduce the energy density of the battery. In addition, if too little conductive agent 5 is added, the internal resistance of the composite current collector 1 cannot be effectively reduced, which will cause a large polarization phenomenon when the battery is charged and discharged with a large current, resulting in an increase in the internal temperature of the battery, which seriously affects the rate performance of the battery. Based on this, the present invention sets the conductive agent 5 in a gradient distribution mode that matches the current density distribution characteristics, thereby gradually reducing the internal resistance of the composite current collector 1 from the second end 1.2 to the first end 1.1 in the direction M1. For example, the negative electrode composite current collector provided by the present invention has an internal resistance (resistivity) from 6×10 -13 Ω·m gradually decreases to 2×10 -13 , the positive electrode composite current collector is in the direction M1 from the second end 1.2 to the first end 1.1, and the internal resistance is from 10×10 -14 Ω·m gradually decreases to 5×10 -14 Compared with the traditional composite current collector (the base film does not contain a conductive agent and its internal resistance is >100Ω·m), it avoids both the polarization problem caused by excessive internal resistance and the problem of low safety performance caused by too low internal resistance.
[0045] Specifically, if Figure 2-Figure 3 As shown, one end of the composite current collector 1, for example, the first end 1.1 is connected to the pole ear 6, and the pole ear 6, as a bridge connecting the electrode and the external circuit, can collect the current generated by the battery active material to form a larger current output. Therefore, the closer to the pole ear 6, the higher the current density (the distribution of the current density is shown in FIG. Figure 3As shown by the arrow in, that is, along the direction M1, the current density gradually increases. Based on this, the present invention sets the conductive agent 5 in a gradient distribution mode that matches the current density according to the distribution characteristics of the current density, for example, more conductive agents 5 are provided in places with high current density, and less conductive agents 5 are provided in places with low current density, thereby: on the one hand, once thermal runaway occurs, the first conductive layer 2 and the second conductive layer 3 will melt rapidly, forming a "circuit-breaking effect", which can effectively prevent the positive and negative electrodes from short-circuiting; on the other hand, once a short circuit or thermal runaway occurs, since the content of the conductive agent 5 matches the distribution of the current density, it can play a "current limiting" role, thereby improving safety. In addition, by setting the conductive agent 5 in a distribution mode that matches the current density according to the distribution characteristics of the current density, the temperature field inside the battery can be made more uniform, the heat dissipation is faster, and the local overheating phenomenon is effectively reduced, thereby improving the stability and safety of the battery. Specifically, areas with high current density are prone to generate heat, and excessive heat will accelerate the aging of battery materials. The present invention can effectively dissipate heat and reduce thermal damage by setting more conductive agents in high-temperature areas, thereby extending the service life of the battery.
[0046] During the battery assembly process, the current collectors of multiple battery cells need to be connected together to form a battery module or battery pack. When the current collectors of the battery cells are stacked, the pole ears of each cell will also be stacked accordingly to form a multi-layer structure. In other words, there will be multiple layers of metal pole ears after the core stacking and lamination. For current collectors made of traditional metal materials (such as metal aluminum or copper foil), the multi-layer pole ears and tab sheets are often ultrasonically welded together. The principle of ultrasonic welding is to reach the melting temperature of the metal through the friction heat between each layer, thereby completing the welding. However, since the base film in the middle of the traditional composite current collector is a polymer material, its thermal conductivity is poor. When the multi-layer pole ears are stacked together to form a stacked core and ultrasonically welded with the tab sheet, due to the poor thermal conductivity of the polymer material, the heat cannot be quickly transferred from the composite current collector on the surface to the composite current collector in the inner layer, because the multi-layer pole ears cannot be ultrasonically welded. The current solution is to use roll welding, that is, a layer of composite current collector and a layer of metal foil are ultrasonically welded together, and then stacked to form a stacked core. However, the efficiency and yield of roll welding are low. The composite current collector 1 provided by the present invention has a greatly improved thermal conductivity due to the addition of a conductive agent 5 to the polymer material base film 4, and the multi-layer tabs can be directly welded together, thereby eliminating roll welding and greatly improving production efficiency.
[0047] Combination Figure 4, the length of the base film 4 is L, the content of the conductive agent 5 at the first end 1.1 is k, wherein 0.2% ≤ k ≤ 2%, the distance from the first end 1.1 to any position of the base film 4 is x, the content of the conductive agent 5 at x is kx, kx = (Lx) / L*k. In this way, the conductive agent 5 can be set to a gradient distribution method that matches the current density distribution according to the characteristics of the current density distribution. Among them, the initial k value can be calculated through simulation, for example, by inputting the conductivity and particle size distribution of the conductive agent, the concentration gradient of the base film, the thickness of the base film and the metal film, and calculating to obtain the k value. Then use this k value to actually make a product test. If the performance requirements are met (through needle puncture and compression tests), the k value is considered to be reasonable; otherwise, it can be increased or decreased by a certain proportion based on the original k value, and then the product test is actually made; until the performance meets the requirements. Studies have found that the range of k is generally between 0.2-2%. Furthermore, if the base film 4 is divided into three equal parts, then x is 1 / 3L, 2 / 3L and L, and the content of the conductive agent 5 at the first end 1.1 is k is 1%, and the content of the conductive agent 5 at 1 / 3L is k 1 / 3L = (L-1 / 3L) / L*k=0.66%, the content k of the conductive agent 5 at 2 / 3L 2 / 3L =(L-2 / 3L) / L*k=0.33%, the content of conductive agent 5 at L is k L is 0, that is, the content of the conductive agent 5 at the second end 1.2 is 0. If the base film 4 is divided into 5 equal parts, the values of x are 1 / 5L, 2 / 5L, 3 / 5L, 4 / 5L and L. The content of the conductive agent 5 at the first end 1.1 is k is 1%, and the content of the conductive agent 5 at 1 / 5L is k 1 / 5L = (L-1 / 5L) / L*k=0.8%, the content of conductive agent 5 at 2 / 5L is k 2 / 5L = (L-2 / 5L) / L*k=0.6%, the content k of the conductive agent 5 at 3 / 5L 3 / 5L =(L-3 / 5L) / L*k=0.4%, the content k of the conductive agent 5 at 4 / 5L 4 / 5L =(L-4 / 5L) / L*k=0.2%, the content of conductive agent 5 at L is K L is 0, that is, the content of the conductive agent 5 at the second end 1.2 is 0. It should be noted that the content of the conductive agent can be the ratio of the mass of the conductive agent in the unit volume of the base film to the total mass of the unit volume of the base film. Studies have found that the more the base film is divided into 4 equal parts, the better the gradient distribution effect is obtained. In particular, the base film can be divided into 3 to 5 equal parts.
[0048] Further, the conductive agent 5 in the above embodiment is one or more of carbon nanotubes, acetylene black and conductive carbon black. The above conductive agent has a very high electronic conductivity and can effectively improve the conductivity of the electrode. In particular, the conductive agent 5 is a carbon nanotube CNT. Since the carbon nanotube has very high mechanical properties, when it is added to the base film 4, it can improve the tensile strength of the composite current collector 1, thereby improving the mechanical strength of the entire electrode.
[0049] Furthermore, in the above embodiment, the thickness of the base film 4 is 3-10 μm, and the thickness of the first conductive layer 2 and the second conductive layer 3 are both 0.5-3 μm. Compared with the current collector of the traditional pure metal material, the thickness of the composite current collector 1 in this range is smaller, so that while having better safety performance, the energy density of the battery can also be improved. In particular, for the positive composite current collector, the thickness of the base film is 4-10 μm, and for the negative composite current collector, the thickness of the base film is 3-10 μm.
[0050] The present invention further provides a lithium ion battery, comprising the composite current collector 1 in any one of the above embodiments.
[0051] By adopting the above technical solution, the battery has high safety performance and good rate performance.
[0052] The present invention also provides a method for preparing a base film 4, which is used to prepare the base film 4 in any of the above embodiments. Figure 5 The slot extrusion coating die 7 shown is prepared, and the method comprises:
[0053] Pretreatment: Conductive agents of different masses are mixed with molten polymer materials to obtain slurries with different contents of conductive agents; the polymer materials are selected from one or more of PET, PP or PI;
[0054] Feeding: Slurries with different contents of conductive agent obtained after pretreatment are fed into the cavity through different feed ports, and then the slurries are mixed to obtain slurries with gradient distribution of conductive agent content;
[0055] Coating: The slurry with a gradient distribution of conductive agent content is extruded and cooled to obtain a base film.
[0056] By adopting the above technical solution, the base film 4 can be quickly prepared, and then the first conductive layer 2 and the second conductive layer 3 are arranged on the upper and lower surfaces of the base film 4 by magnetron sputtering, electroplating or evaporation to obtain the composite current collector 1.
[0057] Combine the following Figure 5 The above-mentioned slit extrusion coating die 7 and the method for preparing the base film 4 are described in detail.
[0058] like Figure 5As shown, the slot extrusion coating die 7 comprises:
[0059] Die head 9: including an upper die head and a lower die head, a coating slit 11 is formed between the upper die head and the lower die head, a cavity is provided inside the lower die head, and an adjusting gasket is provided between the upper die head and the lower die head, and the adjusting gasket is used to adjust the coating thickness;
[0060] Multiple feed ports 8: provided on the lower die head, and the multiple feed ports 8 are connected with the cavity;
[0061] Diaphragm pump: connected to a plurality of feed ports 8, used to pump slurry forming the base film 4, such as the conductive agent 5 and the molten polymer material, into the cavity through the feed ports 8, wherein the polymer material is selected from one or more of PET, PP or PI;
[0062] Coating roller 10 : Close to the die head 9 , the slurry passes through the cavity and is coated on the coating roller 10 along the lip 11 (coating slit) to form the base film 4 . The coating roller 11 is used to receive and transport the base film 4 .
[0063] During coating, the slurry with different conductive agent contents can be pumped to the three slurry feed ports 8 of the coating machine die head through a diaphragm pump, and then flow into the cavity (mold cavity) from the slurry feed port 8, and then stand in the cavity, and then moderately mix, and finally pass through the coating slit 11 to coat the coating roller 10 to obtain the base film 4. Since the feed ports 8 correspond to different positions of the cavity, when the slurries with different conductive agent contents are sent to the cavity along different feed ports 8, the slurries of adjacent parts contact each other, and a gradient distribution can be naturally formed after moderate mixing, and then after coating, a base film 4 with a gradient distribution of conductive agent content can be obtained, for example, from the second end 1.2 to the first end 1.1 in the direction M1, the content of the conductive agent gradually increases. Furthermore, since the feed speed and flow rate of the slurry can be controlled by the diaphragm pump, the spontaneous mixing time in the cavity can be controlled to be within 5-20s, that is, the moderate mixing time is controlled to be within 5-20 seconds, and a better gradient distribution effect can be obtained.
[0064] For example, firstly, conductive agents of different masses, such as CNT, are mixed with molten polymer materials to obtain three slurries with different conductive agent contents, such as 1%, 0.66% and 0.33% of conductive agent CNT contents, respectively. Then, the three slurries are pumped to three feed ports 8 through a diaphragm pump, and then the three slurries flow into the cavity (mold cavity) from the feed port 8. Since the internal cavity of the die 5 is a cavity, the three gradient slurries can be mixed in a small range, and the adjacent parts of the slurries are in contact with each other. After moderate mixing, a gradient distribution can be naturally formed. Then, the slurry is extruded from the lip 11 on the other side of the die, and through the stretching and cooling of the coating roller 10, a base film 4 with a thickness in the range of 3-10um can be obtained, and CNT is distributed in a gradient in the base film 4. For example, in the direction M1 from the second end 1.2 to the first end 1.1, the CNT content increases from 0 to 0.33, 0.66 to 1%.
[0065] Further, the pretreatment step in each of the above embodiments is: putting different masses of conductive agents and molten polymer materials into a double planetary mixer for stirring to obtain slurries with different conductive agent contents, wherein the stirring conditions are: rotation 2000-4000rpm, revolution 15-40rpm, and stirring time 30-40min. Revolution and rotation are carried out simultaneously, revolution can play a role in uniform mixing over a large range, and rotation can exert strong shear force and dispersion on the material, so that the slurry is efficiently dispersed and agglomeration is avoided. The method is simple to operate, highly reliable, and has a good mixing effect. Furthermore, the temperature is maintained at 260 degrees Celsius to 280 degrees Celsius, and the mixture is stirred at 2000-4000rpm, 15-40rpm, and 30-40min of stirring time. In particular, the rotation is 2500-3000rpm and the stirring time is 30-35min.
[0066] Furthermore, the feeding step in the above embodiment includes: feeding the slurries with different contents of conductive agent obtained after pretreatment into the cavity at a rate of 0.2-5 min / L, in particular, at a rate of 1.5 min / L.
[0067] Furthermore, the cavity in each of the above embodiments is used to accommodate slurries with different contents of the conductive agent, and the volume of the cavity is 0.2L-2L. If the volume is too large, the mixing time of the slurry will be too long and the mixing will be too uniform, so that the gradient distribution of the conductive agent content in the slurry is not obvious. If the volume is too small, the mixing time of the slurry will be too short, resulting in the conductive agent content in the slurry presenting several values, rather than gradually changing in the direction M1 from the second end 1.2 to the first end 1.1. In particular, the volume of the cavity is 0.4L-0.6L.
[0068] The present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings.
[0069] Example 1
[0070] Use Figure 5 The slit-type extrusion coating die 7 shown is used to prepare the negative electrode composite current collector 1, and the steps are as follows:
[0071] The production process of the negative electrode composite current collector is as follows:
[0072] Pretreatment: Put 1kg, 0.66kg and 0.33kg of dry powdered carbon nanotube (CNT) conductive agent and 99kg, 99.34kg and 99.67kg of molten polymer material PP (PP material is heated to 240 degrees Celsius to melt) into a double planetary mixer for stirring to obtain slurries with conductive agent contents of 1%, 0.66% and 0.33%, respectively. The stirring parameters are: rotation 2500rpm, revolution 25rpm, and stirring time 30min.
[0073] Feeding: The slurries with different contents of conductive agent obtained after pretreatment are fed into the chamber (the volume of the chamber is 0.4 L) through different feed ports 8 at a rate of 1.5 min / L, and then the slurries are mixed for 5 seconds to obtain slurries with gradient distribution of conductive agent content;
[0074] Coating: The slurry is extruded from the lip 11 on the other side of the die head, stretched and cooled by a coating roller 10 to obtain a base film with a thickness of 4 μm.
[0075] Embodiment 2:
[0076] Use Figure 5 The slit-type extrusion coating die 7 shown is used to prepare the negative electrode composite current collector 1, and the steps are as follows:
[0077] The production process of the negative electrode composite current collector is as follows:
[0078] Pretreatment: Put 1kg, 0.83kg, 0.66kg, 0.33kg and 0.16kg of dry powdered carbon nanotube (CNT) conductive agent and 99kg, 99.17kg, 99.34kg, 99.67kg and 99.84kg of molten polymer material PP (PP material is heated to 260 degrees Celsius to melt) into a double planetary mixer for stirring to obtain slurries with conductive agent contents of 1%, 0.83%, 0.66%, 0.33% and 0.16%, respectively. The stirring parameters are: rotation 2500rpm, revolution 25rpm, and stirring time 30min.
[0079] Feeding: The slurries with different contents of conductive agent obtained after pretreatment are fed into the chamber (the volume of the chamber is 0.4 L) through different feed ports 8 at a rate of 1.5 min / L, and then the slurries are mixed for 5 seconds to obtain slurries with gradient distribution of conductive agent content;
[0080] Coating: The slurry is extruded from the lip 11 on the other side of the die head, stretched and cooled by a coating roller 10 to obtain a base film with a thickness of 4 μm.
[0081] Comparative Example 1:
[0082] The production process of the negative electrode composite current collector is as follows:
[0083] Pretreatment: 100 kg of molten polymer material PP (PP material heated to 260 degrees Celsius to melt) was placed in a double planetary mixer for stirring to obtain a slurry, wherein the stirring conditions were: rotation 2500 rpm, revolution 25 rpm, and stirring time 30 min.
[0084] Feeding: The slurry is fed into the cavity (the volume of the cavity is 0.4 L) along the feed port 8 at a rate of 1.5 min / L;
[0085] Coating: The slurry is extruded from the lip 11 on the other side of the die head, and is stretched and cooled by a coating roller 10 to obtain a PP base film with a thickness of 4 μm.
[0086] Comparative Example 2:
[0087] Pretreatment: 99.5 kg of molten PP material and 0.5 kg of dry powdered carbon nanotubes CNT were added into a double planetary mixer to obtain a slurry with a conductive agent content of 0.5%. The stirring parameters were: revolution 25 rpm, rotation 2500 rpm, 30 min;
[0088] Feeding: The slurry containing the conductive agent obtained after pretreatment is fed into the cavity (the volume of the cavity is 0.4 L) along the feed port 8 at a rate of 1.5 min / L;
[0089] Coating: The slurry is extruded from the lip 11 on the other side of the die head, stretched and cooled by a coating roller 10 to obtain a base film with a thickness of 4 μm.
[0090] The base film obtained in the above-mentioned Example 1-2 and Comparative Example 1-2 and the copper target are sputtered by collision control so that copper is attached to the base film, and then the copper layer is thickened by evaporation to reach 1 μm, and then anti-oxidation treatment is performed to obtain a negative electrode composite current collector with a specification of 4+1+1 (the base film thickness is 4 μm, and the first conductive layer and the second conductive layer are both 1 μm). Then, the surface density and internal resistance of the current collector are tested, and the results are recorded in the following Table 1;
[0091] Then, the battery cell is made. The operation steps are as follows: the graphite negative electrode is coated on the above composite current collector, and the single-sided surface density of the negative electrode is 100g / m 2 , compaction 1.65g / cm 3 , the negative electrode sheet length * width = 126mm * 96mm; the corresponding positive electrode uses ternary NCM811, and the single-sided surface density of the positive electrode is 220g / m 2 , compaction 3.55g / cm 3 , positive electrode length * width = 123mm * 93mm; the number of laminated layers is 40 positive electrode layers and 41 negative electrode layers. After lamination welding, packaging, cell baking, liquid injection, formation, and capacity separation, 30Ah ternary soft package laminated battery application example 1-2 and application comparative example 1-2 are prepared. Then, the internal resistance, battery energy density, and thermal conductivity of the battery thickness direction of application example 1-2 and application comparative example 1-2 are tested, and the battery is subjected to needle puncture and extrusion test tests. The test results are shown in Table 2.
[0092] Table 1
[0093]
[0094] It can be seen from the above table that compared with the composite current collector provided by Comparative Examples 1-2, the composite current collector provided by Examples 1-2 of the present invention has a smaller internal resistance, has passed the needle puncture test and the extrusion test, has good safety performance, and does not require roll welding when welding the pole ears, and ultrasonic welding of the multi-layer pole ears can be directly used.
[0095] The internal resistance of Example 1 is too large, which will cause polarization problems. Example 2 does not set the conductive agent to a gradient distribution method that matches the distribution characteristics of the current density, making it impossible to block the current during the puncture test. Ultimately, it fails to pass the puncture test and has low safety performance.
[0096] By comparing the composite current collectors provided in Example 1 and Example 2, it can be seen that the more the base film is divided into four equal parts, the more the CNT content in the base film is distributed in a gradient, the smaller the impedance of the prepared composite current collector and the internal resistance of the prepared battery, the better the heat dissipation effect, and the better the safety performance.
[0097] Although the present invention has been illustrated and described with reference to certain preferred embodiments of the present invention, it should be understood by those skilled in the art that the above is a further detailed description of the present invention in conjunction with specific embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Those skilled in the art may make various changes in form and details, including making several simple deductions or substitutions, without departing from the spirit and scope of the present invention.
Claims
1. A composite current collector, characterized in that: include: a first conductive layer; a second conductive layer; Base film: located between the first conductive layer and the second conductive layer, the base film comprising a conductive agent; The composite current collector has a first end and a second end arranged opposite to each other along the length direction, the first end is connected to the pole ear, the current density gradually increases from the second end to the first end, and the content of the conductive agent gradually increases; the content of the conductive agent = the mass of the conductive agent in the base film / the total mass of the base film in the area where the conductive agent is located.
2. The composite current collector according to claim 1, wherein the length of the base film is L, the content of the conductive agent at the first end is k, wherein: 0.2%≤k≤2%, the distance from the first end to any position of the base film is x, and the content of the conductive agent at any position x is k x , k x =(Lx) / L*k.
3. The composite current collector according to claim 1, characterized in that: The conductive agent is one or more of carbon nanotubes, acetylene black and conductive carbon black.
4. The composite current collector according to claim 1, characterized in that: The base film has a thickness of 3-10 μm, and the first conductive layer and the second conductive layer have a thickness of 0.5-3 μm.
5. A lithium ion battery, characterized in that: A composite current collector comprising any one of claims 1 to 4.
6. A method for preparing a base film, used for preparing the base film in the composite current collector according to any one of claims 1 to 4, characterized in that: The method adopts a slot-type extrusion coating die for preparation, wherein the slot-type extrusion coating die comprises a cavity and a plurality of feed ports, wherein the plurality of feed ports respectively correspond to different positions of the cavity, and the method comprises: Pretreatment: mixing conductive agents of different masses with molten polymer materials to obtain slurries with different conductive agent contents; the polymer materials are selected from one or more of PET, PP or PI; Feeding: feeding slurries with different contents of conductive agent obtained after pretreatment into the cavity through different feed ports, and then mixing the slurries to obtain slurries with gradient distribution of conductive agent contents; Coating: Extruding and cooling the slurry with a gradient distribution of the conductive agent content to obtain the base film.
7. The preparation method according to claim 6, characterized in that: The pretreatment step is: putting different masses of conductive agents and molten polymer materials into a double planetary mixer for stirring to obtain slurries with different conductive agent contents, wherein the stirring conditions are: rotation 2000-4000rpm, revolution 15-40rpm, and stirring time 30-40min.
8. The preparation method according to claim 6, characterized in that: In the feeding step, the slurry is mixed for 5-20 seconds.
9. The preparation method according to claim 6, characterized in that: The feeding step comprises: feeding the slurries with different contents of conductive agents obtained after pretreatment into the cavity at a rate of 0.2-5 min / L.
10. The preparation method according to claim 6, characterized in that: The volume of the cavity is 0.2L-2L.
